2018
DOI: 10.3390/nu10111614
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin E in Immunity

Abstract: Vitamin E is a fat-soluble antioxidant that can protect the polyunsaturated fatty acids (PUFAs) in the membrane from oxidation, regulate the production of reactive oxygen species (ROS) and reactive nitrogen species (RNS), and modulate signal transduction. Immunomodulatory effects of vitamin E have been observed in animal and human models under normal and disease conditions. With advances in understating of the development, function, and regulation of dendritic cells (DCs), macrophages, natural killer (NK) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
311
0
29

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(342 citation statements)
references
References 85 publications
2
311
0
29
Order By: Relevance
“…Vitamin E includes tocopherols and tocotrienols, and depending on their presence or absence and the position of the methyl group, they are further classified into four different isoforms: α, β, γ, and δ. Vegetable oils contain high amounts of vitamin E [86]. In particular, soybean, sunflower, corn, walnut, cottonseed, palm, and wheat-germ oils are rich in vitamin E, with the proportions of its isoforms varying depending on the type of oil.…”
Section: Vitamin E + Seleniummentioning
confidence: 99%
“…Vitamin E includes tocopherols and tocotrienols, and depending on their presence or absence and the position of the methyl group, they are further classified into four different isoforms: α, β, γ, and δ. Vegetable oils contain high amounts of vitamin E [86]. In particular, soybean, sunflower, corn, walnut, cottonseed, palm, and wheat-germ oils are rich in vitamin E, with the proportions of its isoforms varying depending on the type of oil.…”
Section: Vitamin E + Seleniummentioning
confidence: 99%
“…Calves in the present study had more than adequate serum levels of retinol, 25-(OH)-D 3 , and α-tocopherol by day 14, averaging 255 ng/mL, 97 ng/mL, and 2800 µg/mL, respectively [16], suggesting that deficiency of vitamin E was not the causative factor for this trend. Although vitamin E plays significant roles as an anti-oxidant and an immunomodulatory agent [40,41], a comprehensive study of dairy cows in the Netherlands found that feeding 3000 IU/day of vitamin E combined with high plasma levels of vitamin E at dry-off led to an increased incidence of mastitis [42]. Therefore, high levels of supplemental vitamin E for protracted periods may be detrimental to the host, with a suggested role as a pro-oxidant at high doses.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E includes four isoforms of tocopherols (α, β, γ and δ) and four tocotrienols (α, β, γ and δ). These isoforms cannot be mutually converted and only α-tocopherol meets the need for vitamin E of the human body [51]. The antioxidant property of vitamin E is attributed to the hydroxyl group of the aromatic ring, which gives up one hydrogen atom thus neutralizing radicals or reactive species.…”
Section: Vitamin Ementioning
confidence: 99%